ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE INDEX DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KINERJA PERUSAHAAN - Putra, Idam Manik Setia; Dewayanto, Totok (Diponegoro Journal of Accounting, 2019)
This study aims to exmine the effect of good corporate governance index, sub-index, and institutional ownership as independent variable toward firm performance as dependent variable. This research develops a governance index consisting of 33 indicators to measure the corporate governance index. This study uses secondary data obtained from the Indonesia stock exchange (idx). This research using a sample as many as 269 manufacturing companies registered in BEI year 2015 – 2017. The methods used in this research is purposive sampling method. Statistical techniques used in this study is a multiple regression. The results obtained from this research shows the good corporate governance index, sub-index has the significant positive influence on the firm performance, and institutional ownership has the significant negative influence on the firm performance. However, not all elements of corporate governance appear to have a significant effect on firm performance.